2005
DOI: 10.3354/ame038041
|View full text |Cite
|
Sign up to set email alerts
|

Roles of bacterial community composition in biofilms as a mediator for larval settlement of three marine invertebrates

Abstract: This study investigated (1) the effects of salinity and temperature on the bacterial community composition of developing biofilms, and (2) the responses of marine invertebrate larvae (the polychaete Hydroides elegans and the barnacles Balanus amphitrite and B. trigonus) to these biofilms during settlement (i.e. attachment to a surface and metamorphosis into juveniles). Biofilms developed in a 3 × 3 array of salinity and temperature treatments resulted in different bacterial community compositions (revealed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 39 publications
4
124
1
2
Order By: Relevance
“…However, Qian (1999) demonstrated that after the bacterial density in a biofilm had reached a certain level, reducing the bacterial density by adding antibiotics did not significantly reduce the larval settlement of H. elegans, leading to the hypothesis that the larval settlement of H. elegans is controlled by the presence of specific cues present in the biofilm, regardless of the density of the bacteria. In our study, we observed increases in the bacterial densities of biofilms over time (Figure 1), which is similar to the findings of many earlier studies (Harder et al, 2002a;Huang and Hadfield, 2003;Lau et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, Qian (1999) demonstrated that after the bacterial density in a biofilm had reached a certain level, reducing the bacterial density by adding antibiotics did not significantly reduce the larval settlement of H. elegans, leading to the hypothesis that the larval settlement of H. elegans is controlled by the presence of specific cues present in the biofilm, regardless of the density of the bacteria. In our study, we observed increases in the bacterial densities of biofilms over time (Figure 1), which is similar to the findings of many earlier studies (Harder et al, 2002a;Huang and Hadfield, 2003;Lau et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, bacterial community structure has been suggested as an indicator of habitat suitability for settling H. elegans larvae (Unabia and Hadfield, 1999;Qian et al, 2003;Lau et al, 2005). Our results show that the bacterial community changed more with age than with substratum type (Figure 2).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The formation of biofilm is very important for the adhesion of subsequent fouling organisms. The studies had proved that bacterial biofilm of Pseudoalteromonas spongiae was associated with its induction of larval settlement of the polychaete Hydroides elegans and the settlement was correlated with bacterial density (Lau et al, 2005;Huang et al, 2007), and the reports suggested that the extracellular polymers of benthic diatoms induced larval settlement in the polychaete Hydroides elegans (Lam et al, 2003(Lam et al, , 2005. Similarly, bacterial biofilm promoted the settlement of Ulva spores and Balanus improvisus cyprid (Joint et al, 2002;Tait and Havenhand, 2013).…”
Section: Discussionmentioning
confidence: 99%